The Effect Of Financial Technology, Financial Inclusion, And Innovation On MSME Performance Financial Literacy As Moderation - Sri Ayem; Septiana Wahyu Prasetyaningtyas (UNIVED Press, 2025)
The purpose of this study is to examine the relationship of financial literacy in Magelang district with the in fluence of fintech, innovation and finalcial inclusion on the performance of micro, small and medium enterprises (MSMEs). Data from 84 participants were used, which were then analyzed using IBM SPSS version 23. Small and medium enterprise (MSME) participants in the service, trade, and manufacturing sectors of Magelang district were surveyed for this study. Using purposive sampling as its data research technique, this study utilized quantitative methodology. The researcher collected data by having participants fill out an online survey using Google Forms. The analysis approach used SPSS and MRA. The results obtained show that financial technology and inclusion have a significant positive effect, while innovation is not significant. Financial literacy strengthens business performance related to fintech and innovation, but not financial inclusion. While future researchers can explore additional factors that can be reviewed to see the implications of the goal to strengthen the competitiveness of MSMEs in Magelang District.